(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article underlines the most significant aspects of the Nudge Theory, introduced by Richard Thaler and Cass Sunstein. Analysed from the point of view of philosophy of law and social theory, the so called “libertarian paternalism” rises critics about the compatibility with individual autonomy and liberty. Especially if we consider the possible evolution of the Nudge Theory - the Boosting Approach and the Bio-Moral Enhancement – on specific field, such as criminal law and crime-prevention strategies. It could become the theoretical framework used to discipline the contemporary society, through new “technologies of power” able to promote control without traditional sanctions.